Endeavoring for China's Environment and Development Transformation Three Decades of China Council for International Cooperation on Environment and Development (CCICED) - Zhao, Yingmin; Hanson, Arthur (Springer Nature Singapore : Imprint: Springer, 2024)
This is an open access book. CCICED has been woven into the fabric of China's environmental development for the past 30 years-the length of an entire generation. It is also consistent with the most rapid modernization shift of the nation's economy-environment relationship. This report provides insights into how CCICED operates and its success stories. It also presents a general picture of how changes of China in environmental development have taken place. CCICED at 30 is therefore a helpful account for future directions of sustainable environment.